Influence of Micro- Size Silica Powder on Physical and Rheological Characteristics of Asphalt Binder - H. Zghai, Hussein; H. Joni, Hasan; S. Hassan, Maan (International Journal of Engineering and Technology, 2018)
During the last years, the use of by-product materials, such as micro silica, mS, especially in the area of highway pavement materials has received increasing interest. The experimental work of this research focused on the investigation of the potential use of micro silica powder to enhance the rheological properties of asphalt cement binder. To achieve this aim, mixtures with various contents of micro silica and asphalt were prepared. The asphalt cement and micro silica were first tested. The micro silica powder has been mixed with the asphalt cement at a temperature of 140 Â°C by conventional mechanical mixer at 2000 rpm. Two mixing time durations were implemented to produce the modified asphalt mixtures: 30 and 60 minutes. The mS modified asphalt was then evaluated for the empirical physical and rheological properties including penetration value, softening point temperature, temperature susceptibility, Brookfield Rotational viscosity and ductility. The experimental work results showed that micro silica powder reduces penetration value and increases softening point temperature. Progressive increases in mS content were found to increase Brookfield Rotational Viscosity (RV) and tend to decrease the ductility of the studied specimens. The negative effects of added mS were more pronounced at values more than 4%. Finally, the increase in mixing time duration may slightly lead to good micro silica powder dispersion into the asphalt matrix, but it is the consumption of energy and cost.